Profile of Risk Factors for Venous Thromboembolism (VTE) in Acute COPD Exacerbations at Kolonel Abundjani Bangko Regional Hospital - Mutmainnah, Yaumi; Lindra, Derallah Ansusa (Indonesian Society of Respirology (ISR), 2024)
Background: Acute exacerbation of COPD is characterized by dyspnea and/or cough with worsening sputum production for <14 days. Patients with acute exacerbations of COPD are at increased risk of vascular events, including venous thromboembolism (VTE). VTE risk factor assessment can be carried out using a scoring system to estimate the risk of a patient experiencing VTE before further examination is conducted. Method: This study used a cross-sectional approach. Research subjects were selected from patients diagnosed with acute exacerbation of COPD at Kolonel Abundjani Bangko Regional Hospital from November 2023 to January 2024. Patient data were extracted from medical records, and then patients who were compatible with the inclusion criteria were interviewed using the Wells and Padua criteria. Univariate analysis was conducted to assess the characteristics of VTE risk in acute exacerbation of COPD. Bivariate analysis was utilized to determine the correlation between the exacerbation of COPD and VTE risk using the chi-square test. Results: A total of 20 cases of acute exacerbation of COPD were identified from November 2023 to January 2024. Based on Wells's criteria, as many as 18 patients (90%) were not at risk of developing VTE. Based on Padua criteria, 13 patients (65%) were at low risk and 7 patients (7%) were at high risk of developing VTE. The most common patient characteristics based on the scoring system are an increase in heart rate >100x according to the Wells criteria and the presence of acute infections or rheumatological disorders, which represent the Padua criteria. There is no correlation between acute exacerbation of COPD and VTE risk scoring. Conclusion: The majority of patients with acute exacerbation of COPD are not at risk of developing VTE. There is no correlation between acute exacerbation of COPD and the risk of VTE.